Nonlinear model analysis of all-optical flip-flop and inverter operations of microring laser. (6th February 2018) - Kobayashi, Naoki; Kawamura, Yusaku; Aoki, Ryosuke; Kokubun, Yasuo
Abstract: We explore a theoretical model of bistability at two adjacent lasing wavelengths from an InGaAs/InGaAsP multiple quantum well (MQW) microring laser. We show that nonlinear effects on the phase and amplitude play significant roles in the lasing operations of the microring laser. Numerical simulations indicate that all-optical flip-flop operations and inverter operations can be observed within the same device by controlling the injection current. The validity of our analysis is confirmed by a comparison of the results for numerical simulations with experimental results of the lasing spectrum. We believe that the analysis presented in this paper will be useful for the future design of all-optical signal processing devices.